GAMBARAN TINGKAT KETERGANTUNGAN NIKOTIN PADA ROKOK ELEKTRONIK DIKALANGAN MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS BAITURRAHMAH - Aryaldy Zulkarnaini; Vina Triseptiana; Reno Sari Caniago; Revivo Rinda Pratama; Fauzi Rahmat Dani (Nusantara Hasana Journal, 2023)
Cigarettes are a product that contains addictive substances, which when used can cause dangerous impacts on the health of individuals and society. With the rapid development of technology, currently a new style has emerged for smokers, namely electronic cigarettes. The substance that has the strongest addictive effect is nicotine. This addictive effect of nicotine is usually called Nicotine Dependence. Nicotine dependence or nicotine dependence is a condition where a person involves physical and psychological factors that make it difficult to stop using nicotine. Most of the largest use of electronic cigarettes is among young people of productive age, which if equated to students. This study aims to determine the level of nicotine dependence on electronic cigarettes among Baiturrahmah University medical faculty students. This research uses descriptive analysis with a cross-sectional method using primary data with a sample size of 56 respondents. Univariate data analysis is presented in the form of a frequency distribution. The results of the study showed that the majority of students at the Faculty of Medicine, Baiturrahmah University were smokers with a median age of 21 years, the majority were male (91.1%), started smoking electronically at the age of ≥16 years (91.1%), due to the influence of friends (66.1%), and with an economic level described by income/pocket money > 1 – 2 million (37.5%). The level of nicotine dependence was mostly in the moderate category as many as 30 people (53.6%). The level of nicotine dependence as measured by the Fagerstrom Test in University Medical Faculty students is in the moderate category.